Nilai Sosial Pada Film Happy Go Jenny Oleh Monty Tiwa - Nurul Hasanah Pasaribu; Fita Fatria (Universitas Asahan, 2023)
The film Happy Go Jenny by Monty Tiwa is one of the literary works that has been appreciated by making it into a film. The problem in writing this time is how the social values contained in the film Happy Go Jenny by Monty. In this study using a qualitative descriptive method with data sources derived from the film Happy Go Jenny by Monty Tiwa. For data collection techniques, namely observing and note-taking techniques, the use of data collection techniques is obtained as follows (1) data reduction, (2) data presentation, (3) drawing conclusions. The results of this study contained social values, namely 1) the value of affection, which consists of (1) dedication, (2) mutual help, (3) kinship, (4) loyalty and (5) caring. 2) The value of responsibility, which consists of (1) sense of belonging, (2) obligation, (3) discipline and (4) empathy. 3) The value of harmony in life, which consists of (1) justice, (2) tolerance and (3) cooperation. The author suggests that the results of this study can be used as an illustration for people who watch this film to determine attitudes and actions in living life.